Gelatinases A and B and antioxidant enzyme activity in the early phase of acute myocardial infarction - Gopcevic, K; Rovcanin, B; Kekic, D; Milasinovic, D; Kocic, G; Stojanovic, I (Folia biologica (Praha), 2017)
Oxidative stress plays important roles in the pathophysiology of acute myocardial infarction (AMI). The aim of this study was to investigate the correlation of the oxidative stress status and matrix metalloproteinase activity in AMI patients in comparison to controls. This study included 136 subjects: 68 patients with AMI (42 males/26 females; mean age 58.5 ± 10.5 years) and 68 controls (37 males/29 females; mean age 60.2 ± 12.4 years). Gelatinases A and B were assayed using gelatin zymography, enzyme activities were obtained spectrophotometrically. Gelatinase A and B activities were increased in the AMI patients' group compared to the control. Activities of serum superoxide dismutase (SOD) and xanthine oxidase (XO) were significantly higher in AMI patients (106.53 ± 23.45 U/l, P < 0.001 and 158.18 ± 29.59 U/l, P < 0.001) than in the control group (55.99 ± 10.79 U/l and 79.81 ± 7.93 U/l). The activity of catalase (CAT) in the sera of AMI patients was lower (271.31 ± 7.53 U/l, P < 0.005) than in the control group (305.94 ± 97.28 U/l). Plasma glutathione peroxidase (GPx) and glutathione reductase (GR) in AMI patients were significantly higher (582.47 ± 184.81 U/l, P < 0.001 and 59.64 ± 21.88 U/l, P < 0.001) than in the control group (275.32 ± 104.69 U/l and 47.71 ± 20.05 U/l). The present findings demonstrate activation of gelatinases A and B and oxidative stress markers in the early stage of AMI. Gelatinases, detected at high levels in AMI patients only, indicate their noticeable predisposition for becoming additional biomarkers of the early phase of AMI.
Keywords: senioři; antioxidancia; superoxiddismutasa; protein - isoformy; Protein Isoforms; Male; Xanthine Oxidase; Aged; Middle Aged; Catalase; infarkt myokardu; referenční standardy; Superoxide Dismutase; Myocardial Infarction; glutathionreduktasa; katalasa; mužské pohlaví; želatinasy; Gelatinases; glutathionperoxidasa; Nitrates; Nitrites; dusitany; lidé středního věku; Glutathione Reductase; studie případů a kontrol; Glutathione Peroxidase; xanthinoxidasa; dusičnany; Reference Standards; lidé; Humans; Antioxidants; Case-Control Studies